2008
DOI: 10.1016/j.pbb.2007.08.013
|View full text |Cite
|
Sign up to set email alerts
|

A novel rat strain with enhanced sensitivity to the effects of dopamine agonists on startle gating

Abstract: Background-Compared to outbred Sprague Dawley (SD) rats, inbred Brown Norway (BN) rats exhibit less prepulse inhibition of startle (PPI) at long prepulse intervals, and more PPI at short intervals. Sensitivity to dopaminergic drug effects on PPI differs substantially across strains, and is heritable within SD and other outbred strains. To further understand the heritability of PPI and its sensitivity to dopamine agonists, we assessed PPI and apomorphine sensitivity in SD, BN and F1 (SD×BN) rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 58 publications
4
18
0
Order By: Relevance
“…In this respect, oxytocin has similar effects as the atypical antipsychotics clozapine and quetiapine (Swerdlow et al, 2008) as well as the putative antipsychotic PD149163, which have also been shown to increase PPI in BN rats (Feifel et al, 2011). These data further add to the preclinical evidence supporting the notion that oxytocin has facilitatory effects on sensorimotor gating circuits in the brain and that it also has therapeutic potential in schizophrenia and perhaps other disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, oxytocin has similar effects as the atypical antipsychotics clozapine and quetiapine (Swerdlow et al, 2008) as well as the putative antipsychotic PD149163, which have also been shown to increase PPI in BN rats (Feifel et al, 2011). These data further add to the preclinical evidence supporting the notion that oxytocin has facilitatory effects on sensorimotor gating circuits in the brain and that it also has therapeutic potential in schizophrenia and perhaps other disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Brown Norway (BN) rats have reduced PPI under certain parametric conditions and it has been suggested that these animals represent an appropriate model of schizophrenia, since they exhibit behavioral characteristics frequently reported in schizophrenia patients (Palmer et al, 2000; Swerdlow et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…One to two rats of each sex/litter/prenatal treatment of SS F1 offspring were mated with naïve B rats (Charles River, Wilmington, MA, USA) to generate SB and BS F2 progeny. B is the most phylogenetically divergent inbred rat strain (Swerdlow et al, 2008), and the B and S genomes have been sequenced by the Rat Genome Project and Celera, respectively. All of which increased the chances that we would be able to identify a single nucleotide polymorphism (SNP) between the B and S cDNAs at the Igf2 locus that we could use to measure allele-specific contribution to the expression of hippocampal Igf2 .…”
Section: Methodsmentioning
confidence: 99%
“…Based on known significant sex differences in PPI and IR effects (Powell et al 2002; Lehmann et al 1999; Swerdlow et al 2008) [3133], separate analyses were then pursued in male and female rats. Similar analyses were used to assess IR effects on startle magnitude on PULSE trials, NOSTIM trials, and startle habituation (startle magnitude on PULSE trials in blocks 1 vs. 4).…”
Section: Methodsmentioning
confidence: 99%